214k views
3 votes
-2(y-5)=3y+10-5y PPLLZZ HELPP ASAP

1 Answer

3 votes

Answer:


\huge{ \fbox { \sf{ \: No \: Solution}}}

Explanation:


\star{ \sf{ - 2(y - 5) = 3y + 10 - 5y}}


\text{Step \: 1 \: : \sf{ \: - Distribute \: - 2 \: through \: the \: parentheses \: }}


\mapsto{ \sf{ - 2y + 10 = 3y + 10 - 5y}}


\text{ Step \: 2 \: : Collect \: like \: terms}


\text{Like \: terms \: are \: those \: which \: have \: the \: same \: base.}


\mapsto{ \sf{ - 2y + 10 = - 2y + 10}}


\text{Step \: 3 \: : Move \: 2y \: to \: left \: hand \: side \: and \: change \: its \: sign}


\mapsto{ \sf{ - 2y + 2y + 10 = 10}}


\text{ Step \: 4 \: : Move \: 10 \: to \: right \: hand \: side \: and \: change \: its \: sign}


\mapsto{ \sf{ - 2y + 2y = 10 - 10}}


\mapsto{ \sf{ \cancel{ - 2y} + \cancel{2y} = \cancel{10} - \cancel{10}}}


\sf{∴ \: There \: is \: no \: answer \: to \: the \:given equation.}

Hope I helped!

Best regards! :D

~
\sf{TheAnimeGirl}

User Bo Fjord Jensen
by
5.2k points